Use of Social Accountability Tools and Information Technologies in Monitoring and Evaluation - Sharma, Rajiv (World Bank, Washington, DC, 2012)
This note attempts to cover the basic concepts relating to the use of social accountability and information technology to monitor and evaluate public services and other governance processes that affect citizens. With the help of simple though practical examples that use these concepts, the note explains how to bring a qualitative change in monitoring and evaluation by making the whole process more citizen centered and outcome oriented. In turn, these practices can help improve the quality of service delivery. The note also covers a few country-specific initiatives from India to support the related arguments.